Review Of The Implementation of UMKM Tax and The Level of Taxpayer Compliance After the Implementation of Sin at the Palembang Ilir Timur Primary Service Office - Yuwono, Rusdy; Harnaeni, Nani (SEAN Institute, 2024)
This research is how the growth of compliance with the number of taxpayers in MSME taxpayers after the implementation of the use of KTP or Single Identity Number (SIN) as a Taxpayer Identification Number (NPWP). The purpose of this study is to determine whether after changes in Government Regulations affect the compliance of Taxpayers in fulfilling their obligations. This research includes descriptive research, this thesis writing data collection technique uses the questionnaire method. The data used is primary data. The results showed that MSME actors accepted the application of SIN as an NPWP. This can be seen from the dominant MSME respondents who answered in agreement with indicators of taxpayer understanding, and tax sanctions on the level of taxpayer compliance.